Effect of Microencapsulation Techniques on Physical and Chemical Characteristics of Functional Beverage Based on Red Betel Leaf Extract (Piper crocatum) - Mega Safithri; Susi Indariani; Rosalina Yuliani (Jurnal Kimia Sains dan Aplikasi, 2020)
Functional drinks based on red betel leaf extract have antioxidant activity, but they still have a bitter taste. This study aims to determine the effect of microencapsulation on phenol content, antioxidant activity, and sensory quality of functional drinks based on betel leaf extract. Microencapsulation of functional drinks was made using maltodextrin coatings with concentrations of 10% and 20%. Antioxidant activity was tested by the CUPRAC method. The ready to drink (RTD) functional drink has a total phenolic content and antioxidant activity of 782.30 ± 2.54 mg GAE/g and 1660.19 ± 31.67 µmol Tr/g, respectively. These values are higher than microencapsulated functional drinks with maltodextrin (MM). The microencapsulated functional drink with 10% maltodextrin coating (MM10) is the chosen formulation since it has the smallest particle size (1.283 µm), total phenolic content of 12.90 ± 0.01 mg GAE/g and antioxidant activity of 189.41 ± 1.88 µmol Tr/g. Microencapsulated functional drinks provide sensory quality that is not significantly different (p <0.05) from ready to drink (RTD) drinks.